Impact of Pre-Mortem Factors on Meat Quality: An Update - Gen Kaneko (MDPI AG, 2021)
Meat quality is closely associated with the chemical composition of skeletal muscle and is therefore influenced by the pre-mortem metabolic state of skeletal muscle tissue [...]